2014
DOI: 10.1051/0004-6361/201322713
|View full text |Cite
|
Sign up to set email alerts
|

Dust-enshrouded star near supermassive black hole: predictions for high-eccentricity passages near low-luminosity galactic nuclei

Abstract: Context. Supermassive black holes reside in cores of galaxies, where they are often surrounded by a nuclear cluster and a clumpy torus of gas and dust. Mutual interactions can set some stars on a plunging trajectory towards the black hole. Aims. We model the pericentre passage of a dust-enshrouded star during which the dusty envelope becomes stretched by tidal forces and is affected by the interaction with the surrounding medium. In particular, we explore under which conditions these encounters can lead to per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 79 publications
(112 reference statements)
0
36
0
Order By: Relevance
“…In this paper, we further elaborate on a model of the DSO (see previous models presented in Zajaček et al 2014Zajaček et al , 2016 taking into account the new K s -band measurements and analysis as presented by Shahzamanian et al (2016). By comparing theoretical and numerical calculations with the NIR data, we can explain the peculiar characteristics of the DSO by using the model of a young embedded and accreting star surrounded by a nonspherical dusty envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we further elaborate on a model of the DSO (see previous models presented in Zajaček et al 2014Zajaček et al , 2016 taking into account the new K s -band measurements and analysis as presented by Shahzamanian et al (2016). By comparing theoretical and numerical calculations with the NIR data, we can explain the peculiar characteristics of the DSO by using the model of a young embedded and accreting star surrounded by a nonspherical dusty envelope.…”
Section: Introductionmentioning
confidence: 99%
“…(i) core-less cloud/streamer (Gillessen et al 2012;Burkert et al 2012;Schartmann et al 2012;Pfuhl et al 2015;Schartmann et al 2015) Article (ii) a dust-enshrouded star (Murray-Clay & Loeb 2012;Eckart et al 2013;Scoville & Burkert 2013;Ballone et al 2013;Zajaček et al 2014;De Colle et al 2014;Valencia-S. et al 2015;Ballone et al 2016) (iii) binary/binary dynamics Prodan et al 2015;Witzel et al 2014) The scenarios (i), (ii), (iii), and a few more are summarized in Table 1 with corresponding references.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have also shown that G2 survived its pericenter passage as a compact source, which might be a clue that G2 is a star enshrouded by gas and/or dust (Witzel et al 2014;Valencia et al 2015). This scenario was modeled analytically (Miralda-Escudé 2012; Scoville & Burkert 2013) and explored with the help of numerical simulations (Ballone et al 2013;De Colle et al 2014;Zajaček et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The authors predicted that the cloud should be disrupted near its pericenter d passage. However, subsequent observations showed that the object was not disrupted after the pericenter passage, therefore, it was concluded that it is a dust-enshrouded star [76,77,78] or a young star [79].…”
Section: Observations Of the Galactic Centermentioning
confidence: 99%